APLIKASI PENDEKATAN BERMAIN UNTUK MENINGKATKAN EFEKTIVITAS PEMBELAJARAN BOLA VOLI KELAS VIII SMP AL ISLAM 1 SURAKARTA - Hendarto, Singgih (Pendidikan Dan Kepelatihan Olahraga, 2010)
The purpose of this study was to determine whether the correct application Playing approach can improve the effectiveness of learning volleyball junior class VIII Yunior High Scool Al Islam 1 Surakarta. This research is a classroom action research (classroom action research) that use a qualitative approach because it uses a direct data source as a scientific background, descriptive data in the form of words or sentences, olef limited focus. Conducted data analysis and more interested in the inductive process rather than results. Type of research used is participatory action research, researchers directly involved from the beginning to the end of the study. In this study, the role of researchers in the field to plan activities, carry out action learning, observing the implementation of learning, conducting interviews with research subjects, and finally reported the results research and data analysis has been conducted, the conclusion can be obtained as follows: Learning the game approach to volleyball is a great way to learn to play that emphasizes the ability to raise the concept of tactics with technical skills. Playing the game approach is to increase students' awareness about the concept of playing through application of appropriate techniques to problem situations in a real game. Therefore, learning to play approach, can enhance morale and motivation of students in learning, allowing students to be more active in the movement. Active students in the learning process can increase the frequency of students in the more movement of students to repeat the movement of physical condition and skills growing student movement. Learning volleyball game play approach provides a more effective stimuli in the form of physical conditions and elements of the movement patterns volleyball game. The results of the application's ability 48.896%.